Odpowiedzi

2010-03-11T15:24:55+01:00
A)4x(x-7y)-8(2x-4y)+3(x-3y)+13
4x² - 28xy - 16x + 24y + 3x - 9y +13 = 4x² - 28xy - 13x + 15y +13

b) 5a(-2b+1)+3b(9a-2)-(a-2b)
-10ab + 5a + 27ab - 6b - a + 2b = 17ab + 4a + 4b

c)2,5x(4y-z)-4,5y(2x-z)+3,5z(5y-2y)
10xy - 2,5z - 9xy + 4,5z + 17,5yz - 7yz = xy + 2z + 10,5yz

1 5 1
2010-03-11T15:25:53+01:00
A)4x(x-7y)-8(2x-4y)+3(x-3y)+13=4x²-28xy-16x+32y+3x-9y+13=
=4x²-28xy-13x+23y+13

b)5a(-2b+1)+3b(9a-2)-(a-2b)=-10ab+5a+27ab-6b-a+2b=37ab+4a-4b

c)2,5x(4y-z)-4,5y(2x-z)+3,5z(5y-2y)=
=10xy-2,5xz-9xy+4,5yz+17,5yz-7yz=xy-2,5xz+15yz
1 5 1
2010-03-11T15:29:38+01:00
A).4x(x-7y)-8(2x-4y)+3(x-3y)+13=4x² - 28xy - 16x + 24y + 3x - 9y +13 = 4x² - 28xy - 13x + 15y +13

b). 5a(-2b+1)+3b(9a-2)-(a-2b)=-10ab+5a+27ab-6b-a+2b=37ab+4a-4b


c).2,5x(4y-z)-4,5y(2x-z)+3,5z(5y-2y)=10xy-2,5xz-9xy+4,5yz+17,5yz-7yz=xy-2,5xz+15yz

1 5 1